Batteries: Advanced Phosphorus‐Based Materials for Lithium/Sodium‐Ion Batteries: Recent Developments and Future Perspectives (Adv. Energy Mater. 13/2018). Issue 13 (4th May 2018) - Fu, Yanqing; Wei, Qiliang; Zhang, Gaixia; Sun, Shuhui
Abstract : Phosphorus is an emerging candidate for anode materials in both lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs), especially for electric vehicles. In article number1702849, Gaixia Zhang, Shuhui Sun and co‐workers present an overview of the latest achievements in the field, illustrating the rational design strategies, with special emphasis on demonstrating the mechanisms for the structure‐related performance improvements in targeted applications.